2012
DOI: 10.5455/jihp.20121105123701
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Effects of Varied Fluoride Concentration on Cerebrum in Albino Rats

Abstract: Fluorides have been a cause of concern for scientists and environmentalists for the long because of their harmful effects on the human and animal life but the problem was highlighted during the twentieth century because of great increase in the human population and industrialization. Since fluorides accumulate in calcified and hard tissues of the body such as bone and teeth and can be detected easily in these tissues, so most of the previous studies focused on the effects of fluorides on these tissues. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…However, during the past decade researchers all over the world have felt that there is a need to study the effects of fluorides on other tissues of the body including central nervous system, as the fluorides are known to cross blood brain barrier. [21] In the present study, the animals of negative control subgroup showed a significant increase in the body weight at the end of the experiment. This was in agreement with Soliman et al [18] who reported that balanced diet feeding resulted in a significant increase in the body weight of rats.…”
Section: Discussionsupporting
confidence: 49%
“…However, during the past decade researchers all over the world have felt that there is a need to study the effects of fluorides on other tissues of the body including central nervous system, as the fluorides are known to cross blood brain barrier. [21] In the present study, the animals of negative control subgroup showed a significant increase in the body weight at the end of the experiment. This was in agreement with Soliman et al [18] who reported that balanced diet feeding resulted in a significant increase in the body weight of rats.…”
Section: Discussionsupporting
confidence: 49%
“…Some pyramidal neurons showed chromatolysis (Trivedi et al, 2012), and were shrunken with vacuolation around them. These results are in accord with the results of Ge et al(2005), Fattah et al, (2010), Hamid et al, (2012 and Shashi and Sharma (2015), who documented distinct morphological alterations in the brain including effects on neurons of the cerebrum. In other study on amygdala, motor cortex, cerebellum, hippocampus (Shivarajashankara et al, 2002), and the cerebrovascular integrity after chronic administrations of sodium fluoride or aluminum fluoride (Varner et al, 1998) comparable results was obtained.…”
Section: Resultssupporting
confidence: 91%